2016
DOI: 10.1111/anu.12440
|View full text |Cite
|
Sign up to set email alerts
|

Effect of diets low in fish oil and supplemented with chlorogenic acid on fatty acid composition and lipid metabolism in Atlantic salmon (Salmo salarL.)

Abstract: This study aimed to test the use of chlorogenic acid (CGA), a natural antioxidant, which might act improving the retention of eicosapentaenoic (EPA) and docosahexaenoic (DHA) fatty acids. Fish were fed one of three experimental diets. A diet with 160 g kg−1 fish oil (FO) and 80 g kg−1 vegetable oil (VO) was used as a positive control with high n‐3 long‐chain polyunsaturated fatty acids (LC)‐PUFA, a diet containing 40 g kg−1 FO and 200 g kg−1 VO was used as a negative control for low n‐3 LC‐PUFA and 1 g kg−1 CG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 51 publications
1
5
1
Order By: Relevance
“…The antioxidant capacity of Chlorogenic acid may delay the oxidation of lipids. And it not only promotes β-oxidation of lipids but also induces n-3 LC-PUFA syntheses via transcriptional control of fatty acid elongases and desaturases through increased the expression of the perxisome proliferator-acivated receptor ɑ (Rakhshandehroo et al, 2007;Kühn et al, 2017). However, it did not showed dose-dependent between chlorogenic acid addition level and muscle n-3 LC-PUFA level in this study.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…The antioxidant capacity of Chlorogenic acid may delay the oxidation of lipids. And it not only promotes β-oxidation of lipids but also induces n-3 LC-PUFA syntheses via transcriptional control of fatty acid elongases and desaturases through increased the expression of the perxisome proliferator-acivated receptor ɑ (Rakhshandehroo et al, 2007;Kühn et al, 2017). However, it did not showed dose-dependent between chlorogenic acid addition level and muscle n-3 LC-PUFA level in this study.…”
Section: Discussioncontrasting
confidence: 60%
“…This may be due to the chlorogenic acid in EUO. Kühn et al (2017) found that there was a tendency to increase C22:6n-3 levels in the liver of Atlantic salmon fed chlorogenic acid diets. The chlorogenic acid is an ester of caffeic acid and quinic acid present in coffee and various other plants, such as EUO, fruits, vegetables, black teas, soybeans and wheat (Sun et al, 2017b).…”
Section: Discussionmentioning
confidence: 95%
“…The same letter indicates no statistical differences (P > 0.05), but different letters indicate statistically significant differences (P < 0.05) performance. Similarly, the supplementation of EB, EL, CGA and QC in diets also improved the growth of shrimp (Liu et al, 2013), large yellow croaker Larimichthys crocea (Huang et al, 2021), Atlantic salmon Salmo salar (Kühn et al, 2017) and tilapia (Zhai & Liu, 2013), respectively. The dietary effects of AU and PDG on the growth of aquatic animals have not been reported yet.…”
Section: The Mrna Expression Of Collagen Metabolism-related Genes In ...mentioning
confidence: 86%
“…In grass carp, dietary Eucommia bark (EB, Xu et al ., 2018), Eucommia leaf (EL, Yang et al ., 2020), CGA (Sun et al ., 2017) and QC (Xu et al ., 2019) have been reported to promote the growth performance. Similarly, the supplementation of EB, EL, CGA and QC in diets also improved the growth of shrimp (Liu et al ., 2013), large yellow croaker Larimichthys crocea (Huang et al ., 2021), Atlantic salmon Salmo salar (Kühn et al ., 2017) and tilapia (Zhai & Liu, 2013), respectively. The dietary effects of AU and PDG on the growth of aquatic animals have not been reported yet.…”
Section: Discussionmentioning
confidence: 99%
“…Aquaculture Nutrition especially in the treatments of 600-800 mg ChA/kg diet, as the levels of MDA were lower in these groups compared to unsupplemented fish. MDA is generated upon peroxidation of lipids in the cell and thus is generally considered one of the main indicators of oxidative stress in fish and other vertebrates [27,32,60,61,[85][86][87][88]. The ameliorating effects of ChA on oxidation stress may be due to its antioxidant properties, which can be attributed to the presence of phenolic functional groups in its biochemical composition [25,89,90].…”
mentioning
confidence: 99%